Campanula dimorphantha Schweinf. Additions to Angiosperm flora of Doaba region of Punjab, India - Rai Singh; Varinder Sharma (Plantae Scientia, 2023)
Campanula dimorphantha Schweinf. is documented first time from Doaba region of Punjab, India. This study will be useful for Botanists, taxonomists, researchers etc. for identification of species.